Molecular characterization of genomic regions for adult plant resistance to stem rust in a spring wheat mapping population - Rauf, Yahya; Bajgain, Prabin; Rouse, Matthew N.; Khanzada, Khalil A.; Bhavani, Sridhar; Huerta Espino, Julio; Singh, Ravi P.; Imtiaz, Muhammad; Anderson, James A. (Scientific Societies, 2022)
Stem rust caused by Puccinia graminis Pers.:Pers. f. sp. tritici Erikss. & E. Henn. is an important disease of bread (Triticum aestivum L.) and durum (T. turgidum spp. durum Desf.) wheat in Ethiopia. The frequent emergence of new P. graminis f. sp. tritici virulent races remains a major constraint to wheat production. Wheat stem rust surveys are carried out annually during both the main (late August through October) and off-seasons (June and July) in Ethiopia. During the annual 2017 main season survey, a total of 60 stem rust samples were collected from farmer’s field in the major wheat growing areas of Oromia and Amhara Regions. Forty-eight single pustule isolates were derived from these samples at Ambo Plant Protection Research Center (Ethiopia) and multiplied on susceptible wheat cultivar McNair 701. Physiological race analysis was performed using the 20 North American stem rust differential lines following the standard protocol of Jin et al. (2008). Race analysis was repeated up to seven times until the race was confirmed. Ten isolates collected from different fields in four zones were determined to be race TTRTF (Supplementary Table S1). P. graminis f. sp. tritici race TTRTF was virulent to wheat differential lines containing Sr5, Sr21, Sr9e, Sr7b, Sr11, Sr6, Sr8a, Sr9g, Sr36, Sr9b, Sr17, Sr9a, Sr9d, Sr10, SrTmp, Sr38, SrMcN and avirulent on lines with Sr30, Sr24, Sr31 (Supplemental Table S2). Isolates belonging to this race were derived from stem rust samples from commercial wheat cultivars Digelu, Danda’a, Pavon 76, and Israel, as well as Triticale. Urediniospores of the 48 isolates were sent to the Cereal Disease Laboratory, St. Paul, MN for genotyping. DNA was extracted from spores (Olivera et al. 2015) and genotyped using 17 selected single nucleotide polymorphism markers (Szabo unpublished data). All isolates that were race typed as TTRTF were genotyped as MLG.04 (Clade III-B) and were identical to reference isolates (Supplemental Fig S1). P. graminis f. sp. tritici race TTRTF was first identified from wheat stem rust collections made in 2014 from Akhalkalaki, Georgia (Olivera et al. 2019). In addition to the virulences described above, P. graminis f. sp. tritici race TTRTF has virulence to several other important stem rust resistance genes but, these were not tested. Severe epidemics of wheat stem rust on durum wheat in Italy in 2016 and 2017 were caused by race P. graminis f. sp. tritici TTRTF (Patpour et al., 2018). The same race has also been reported in Hungary (Olivera et al. 2019) and Egypt (Samar and Szabo, 2018). However, this is the first confirmation of P. graminis f. sp. tritici race TTRTF in Ethiopia. These results indicate P. graminis f. sp. tritici TTRTF with complex virulence is spreading rapidly and has now become established in Ethiopia. Further spread is considered likely and close monitoring is required.